Microstructure and erosive wear behavior of weld deposits of high manganese electrode - Yildizli, Kemal; Eroglu, Mehmet; Karamis, M. Baki (Elsevier Science Sa, 2007)
Low carbon steel plates were surfaced with single, double and triple pass bead on-plate welds using the shielded metal arc welding technique with a high manganese electrode. After deposition, the microstructure, hardness and erosive wear behavior of the deposit layers were investigated. Erosion tests were conducted at impact angles of 30, 60 and 90 degrees using angular erodent with particle velocity of 30 m/s. From the results of microstructural investigation and hardness measurement, when each layer was superficially processed by the same electrode, it was seen that the microstructure changed from martensite with retained austenite to austenite. Hardness values decreased as the number of layer was increased. This was related to the higher contents of Mn and C as a result of increased layer number. The erosion test results showed that the erosion rate varied as a function of the impact angle as well as the number of the layers. The highest erosive wear occurred at 90 degrees for all layers. Taking into consideration the erosion wear resistance, it was consequently found that the deposition with single pass gave good results for a low speed erosion test. (C) 2007 Elsevier B.V. All rights reserved.
5th International Conference on Tribology -- JUN 15-18, 2005 -- Kragujevac, SERBIA MONTENEG
Keywords: microstructure; hardness; high manganese electrode; solid particle erosion; hardfacing